2015
DOI: 10.1093/czoolo/61.4.569
|View full text |Cite
|
Sign up to set email alerts
|

The heart rate - breathing rate relationship in aquatic mammals: A comparative analysis with terrestrial species

Abstract: Aquatic and semi-aquatic mammals, while resting at the water surface or ashore, breathe with a low frequency (f) by comparison to terrestrial mammals of the same body size, the difference increasing the larger the species. Among various interpretations, it was suggested that the low-f breathing is a consequence of the end-inspiratory breath-holding pattern adopted by aquatic mammals to favour buoyancy at the water surface, and evolved to be part of the genetic makeup. If this interpretation was correct it coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 78 publications
2
23
0
Order By: Relevance
“…29,33,37 By comparison, the adult Gallus gallus averages 190 beats per minute 46 and 22.5 breaths per minute. 47 Hence, the normoxic fH/fB in the embryos, ~6 beats per breath (Table 3), was lower than in the adult (~8) and higher than in most mammals (~4.5 48 ). These differences should reflect the fact that in adult birds, the cross-current respiratory system is a more efficient gas exchanger than in mammals and requires lower pulmonary ventilation, 33,49 an efficiency probably not yet reached by the embryo at hatching time.…”
Section: Resting Values and Variability In Normoxiamentioning
confidence: 90%
“…29,33,37 By comparison, the adult Gallus gallus averages 190 beats per minute 46 and 22.5 breaths per minute. 47 Hence, the normoxic fH/fB in the embryos, ~6 beats per breath (Table 3), was lower than in the adult (~8) and higher than in most mammals (~4.5 48 ). These differences should reflect the fact that in adult birds, the cross-current respiratory system is a more efficient gas exchanger than in mammals and requires lower pulmonary ventilation, 33,49 an efficiency probably not yet reached by the embryo at hatching time.…”
Section: Resting Values and Variability In Normoxiamentioning
confidence: 90%
“…2). Past work has shown that the f H f R −1 is significantly greater not only in cetaceans but also in a larger range of marine mammals (Mortola, 2015). It was suggested that this is a non-respiratory adaptation to provide additional buoyancy.…”
Section: Cardiorespiratory Coupling In Inactive Marine and Terrestriamentioning
confidence: 99%
“…Aquatic mammals have special adaptations of the respiratory and cardiovascular systems that are associated with diving (Mottishaw et al 1999;Bostrom et al 2008;Mortola 2015), and that confer increased hypoxia tolerance (Sergina et al 2015;Hoff et al 2017) and oxygen storage (Nery et al 2013). Interest in conservation of marine mammals, in regard to anthropogenic stress, has also generated studies of their stress physiology (Wright et al 2007;Atkinson et al 2015), and the effect of climate change on these mammals (Thiemann et al 2008).…”
Section: Life Stylesmentioning
confidence: 99%